2017
DOI: 10.1038/s41467-017-02082-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased ionization supports growth of aerosols into cloud condensation nuclei

Abstract: Ions produced by cosmic rays have been thought to influence aerosols and clouds. In this study, the effect of ionization on the growth of aerosols into cloud condensation nuclei is investigated theoretically and experimentally. We show that the mass-flux of small ions can constitute an important addition to the growth caused by condensation of neutral molecules. Under atmospheric conditions the growth from ions can constitute several percent of the neutral growth. We performed experimental studies which quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 39 publications
2
77
0
2
Order By: Relevance
“…Lockwood et al [44] clearly showed the relevance of solar activity indicators for the heliospheric cosmic ray modulation potential and the associated cooling and warming of the earth during the past 400 years. The causal chain between solar magnetic activity, cosmic ray flux hitting the earth, cloud formation potential, and mean global temperature has been shown by Svensmark and Friis-Christensen [45] and was convincingly defended against premature critics [46].…”
Section: Forage Groups 80mentioning
confidence: 98%
“…Lockwood et al [44] clearly showed the relevance of solar activity indicators for the heliospheric cosmic ray modulation potential and the associated cooling and warming of the earth during the past 400 years. The causal chain between solar magnetic activity, cosmic ray flux hitting the earth, cloud formation potential, and mean global temperature has been shown by Svensmark and Friis-Christensen [45] and was convincingly defended against premature critics [46].…”
Section: Forage Groups 80mentioning
confidence: 98%
“…The possible rise on the ionization levels on the atmosphere due to the increased CR flux caused by the SN explosion may possibly be connected to climate change (Svensmark et al, 2017), but this is a controversial claim. Here, we are concerned with the effects of the muons.…”
Section: Estimates Of Biological Effects and The Pliocene-pleistocenementioning
confidence: 99%
“…For all these reasons, evaluation of effects from the SN is complicated. It may possibly be connected to climate change [24], but this is a controversial claim. Here, we are concerned with the effects of the muons.…”
Section: Estimates Of Biological Effects and The Pliocene-pleistocenementioning
confidence: 99%